Cardiac Implantable Electronic Device‐Related Infection and Extraction Trends in the U.S. Issue 3 (15th February 2017) - SRIDHAR, ARUN RAGHAV MAHANKALI; LAVU, MADHAV; YARLAGADDA, VIVEK; REDDY, MADHU; GUNDA, SAMPATH; AFZAL, RIZWAN; ATKINS, DONITA; GOPINATHANAIR, RAKESH; DAWN, BUDDHADEB; LAKKIREDDY, DHANUNJAYA R.
Abstract : Background: Implantation of cardiac implanted electronic device (CIED) has surged lately. This resulted in a rise in cardiac device‐related infections (CDI) and inevitably, lead extractions. We examined the recent national trend in the incidence of CIED infections and lead extractions in hospitalized patients and associated mortality. Methods: Using the Nationwide Inpatient Sample for the years 2003–2011 we identified patients diagnosed with a CDI‐associated infection as determined by discharge ICD‐9 diagnostic codes. We examined the trend of device‐related infections overall and in different subgroups. We studied mortality associated with device infections, lead extractions, associated costs, and length of stay. Results: There is a significant increase in the number of hospitalizations due to CDI from 5, 308 in the year 2003 to 9, 948 in 2011. Males (68%), Caucasians (77%), and age group 65–84 years (56.4%) accounted for majority of CDI. The mortality associated with CDI was 4.5 %, and was worse in higher age groups (2.5% in 18–44 years compared to 5.3% in 85+ years, P < 0.001). Average length of stay was unchanged over the years remaining at 13.6 days; however, mean hospitalization charges increased from 91, 348 in 2003 to 173, 211 in 2011 (P < 0.001). Among all lead extraction procedures, the percentage of patients undergoing lead extraction secondary to CDI also increased from 2003 (59.1%) to 2011 (76.7%), P‐value < 0.001. Conclusions: Healthcare burden associated with CDI infections and associated lead extractions has significantly increased in the recent years. Despite an increase in cost associated with CIED infections, mortality remains the same, and is higher in older patients.